Application of quality-by-design approach to optimize diallyl disulfide-loaded solid lipid nanoparticles. (3rd April 2017) - Talluri, Siddhartha Venkata; Kuppusamy, Gowthamarajan; Karri, Veera Venkata Satyanarayana Reddy; Yamjala, Karthik; Wadhwani, Ashish; Madhunapantula, SubbaRao V.; Pindiprolu, Saikiran S. S.
Abstract: The current work was carried out by the principles of quality-by-design approach to develop an optimized solid lipid nanoparticles (SLNs) formulation of diallyl disulfide (DADS) through systematic statistical study. And its antitumor activity of DADS was also evaluated on breast cancer cell lines. To understand the effect of formulation variables (critical parameters) on the responses (critical quality attributes) of SLN, a 3-factor, 3-level Box–Behnken design, was explored to predict the responses such as particle size (Y1) and % entrapment efficiency (EE) (Y2) when concentration of surfactant (X1), amount of lipid (X2), and volume of solvent (X3) were selected as independent variables. Particle size analysis revealed that all the batches were within the nanometer range. DADS was released from the SLN much more rapidly at pH 4.5 than at pH 7.4, which is a desirable characteristic for tumor-targeted drug delivery. The cytotoxicity, reactive oxygen species (ROS), determination revealed that the antitumor activity of DADS is enhanced with SLN compared to DADS-free drug, and apoptosis is the mechanism underlying the cytotoxicity. The present study indicated the remarkable potential of DADS-SLN in enhancing the anticancer effect of DADS in breast cancer cells in vitro .